Achievement Test of Education Students in Assessment of Student Learning - Mark Angelo C. Reotutar; Norie T. Tactay; Muhammad Ridwan (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
The study attempted to determine the level of achievement of the selected education students in Assessment of Student Learning. It was also tested if there existed a significant differences between and among the achievement of the four groups of respondents. The samples of the study were education students enrolled in Assessment of Student Learning. The first group of respondents were the Bachelor of Secondary Education (BSEd) students. The second group were the Bachelor in Elementary Education (BEED) group. The third were the students enrolled in Bachelor in Industrial Education (BSIE) students. A 25-item test which was adopted from assessment books was used check the level of achievement of the respondents. Mean, Standard Deviation, ANOVA, and Sheffe’s Test were used as a statistical tools to treat and analyze the data gathered. The Bachelor in Industrial Education and Bachelor of Elementary Education groups performed very good while the Bachelor of Secondary Education and Bachelor in Library and Information Science groups were at good level. The overall performance of the four groups of respondents were very good. There exist significant differences between and among the means of the achievement of the respondents. Based from the findings of the study, the researcher concluded that the level of achievement of the respondents in Assessment of Student Learning was very good. In addition, there existed significant differences between and among the achievement of the four group of respondents. The study recommends that students enrolled in assessment should be encourage to be outstanding in their performance and a further study using other respondents be conducted to validate the results.